2005
DOI: 10.1017/s0144686x04002739
|View full text |Cite
|
Sign up to set email alerts
|

The impact of retirement on physical activity

Abstract: Most adults do not achieve the levels of physical activity currently recommended for a healthy lifestyle. Population surveys suggest that there is a linear decline of activity levels with age, yet physical activity has many health benefits for older adults. If these are to be more widely adopted among older people, health policy and promotion require an understanding of the factors that influence decreasing activity with age. This study examined the patterns of physical activity of 699 participants in the West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
3
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 16 publications
10
118
3
4
Order By: Relevance
“…The findings of some studies have shown that entering retirement increases engagement in leisure activities, and thus support activity theory (Iwasaki and Smale 1998;Janke et al 2006;Van den Bogaard et al 2013). However, the results of other studies have indicated that retirement does not increase engagement in leisure activities (Bosse and Ekerdt 1981;Rosenkoetter et al 2001;Talyor et al 2004;Agahi et al 2006;Berger et al 2005). The findings of still other studies have shown that engagement in leisure activities declines with increasing age, and thus support disengagement theory (Griffin and McKenna 1999).…”
Section: Preretirement Leisure and Postretirement Leisuresupporting
confidence: 43%
“…The findings of some studies have shown that entering retirement increases engagement in leisure activities, and thus support activity theory (Iwasaki and Smale 1998;Janke et al 2006;Van den Bogaard et al 2013). However, the results of other studies have indicated that retirement does not increase engagement in leisure activities (Bosse and Ekerdt 1981;Rosenkoetter et al 2001;Talyor et al 2004;Agahi et al 2006;Berger et al 2005). The findings of still other studies have shown that engagement in leisure activities declines with increasing age, and thus support disengagement theory (Griffin and McKenna 1999).…”
Section: Preretirement Leisure and Postretirement Leisuresupporting
confidence: 43%
“…This procedure is in line with research suggesting that the recommended 30 min or more of moderate intensity physical activity can be accumulated from various activities. Such an "active living" approach is considered particularly appropriate for older adults (Berger et al, 2005). Body mass index (BMI) was calculated from reports of both weight and height in the postal questionnaire, and the WHO criteria of underweight or normal weight (<25.0) versus overweight or obese (≥25.0) were used.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of studies examining effects of retirement on physical activity indicate that the frequency and duration of outdoor activities such as walking and biking appear to increase when one quits work, or at least show a smaller reduction than to those who continue working (Berger, Der, Mutrie, & Hannah, 2005;Gallo, 2013;Sjosten et al, 2012;Solem, 2012). This is in line with the demand for health theory.…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…They did not include a measure of disability but found that health status at baseline was related to both decline and improvement in physical activity. Berger et al (2005) analysed patterns of changes in physical activity in an older population using the most recent recommendations from American College of Sports Medicine, which suggest that ''all people over the age of 2 years should accumulate at least 30 min of endurance type physical activity, of at least moderate intensity, on most-preferably all-days of the week '' (Physical Activity and Health 1996;Pedersen and Saltin 2003). They found that changes in disability was the most important factor related to changes in physical activity.…”
Section: Introductionmentioning
confidence: 99%